Three new species of Synagelides Strand, 1906 from China (Araneae: Salticidae) - Liu, Keke; Chen, Zhiwu; Xiao, Yonghong; Xu, Xiang; Peng, Xianjin (Zootaxa, 2017)
The new species Synagelides jinggangshanensis sp. nov. (♀), S. tangi sp. nov. (♂ and ♀) and S. yinae sp. nov. (♀) from China are described. Distribution data, detailed morphological characteristics, illustrations of body and copulatory organs are presented.